An Ethnographic Study of the Ritual Practices of Magars of Chaunna Kuriya, Myagdi, Nepal - Roka, Lal Kumari (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This ethnographic study explores the ritual practices of the academically under-researched area of the Magars of Chaunna Kuriya, Myagdi, Nepal. This study employed conversational interviews, observations, and Focused Group Discussions (FGDs) to determine how these rituals are performed and adopted Barth’s (1969) assertion that ethnic groups are maintained through boundaries rather than cultural content alone. The Chaunna Kuriya Magars’ practices, such as restricting outsiders’ presence during rituals, serve as active mechanisms for demarcating and preserving group identity. The key findings include historical traditions of ritual practices; collective assets of ritual practices; linkage of ritual practices with seasons, weather, and natural resources; connection of ritual functions with nature; and the tie of ritual practices with livelihood. As a nodal study of ritual practices, this research aids young scholars, academicians, policymakers, and government authorities in understanding rituals in general, and those of the Magars of Chaunna Kuriya in particular.